Langmuir and Freundlich Isotherm Model for Adsorption of Betacyanin Pigment onto Spun Silk and Acrylic Yarns - Norasiha, Hamid; Mimi Sakinah, A. M.; Mazrul Nizam, Abu Seman (2016)
A study on the equilibrium adsorption of the betacyanin pigment extracted from the dragon fruit peel onto spun silk and acrylic yarn was conducted. The equilibrium adsorption data were tested into Langmuir and Freundlich isotherms at different temperatures. By linearizing the equilibrium isotherm, the best isotherm model equation was determined using coefficient of determination (R2 value). It was found that the equilibrium data was fitted well by the Freundlich isotherm model for acrylic yarn at temperature of 30°C with R2 of 0.97.